(untitled) (Tempo e Argumento, 2021)
The teaching of History asserts itself, today, as an important contribution to the integral formation of younger generations, as a facilitator of a more conscious understanding of the contemporary social and cultural realities, as an enhancer of various skills for the interpretation of historical matters and, therefore, of a more enlightened democratic participation. On the other hand, the intentional use of Literature might provide a multiperspective and human way of analyzing and understanding social phenomena, everyday common history, different times and places. Through that evident interaction between areas of knowledge, it is possible to understand the possibility of developing, with coherence, dynamics of curricular articulation. In that sense, this investigation results from a study developed with Portuguese children attending the 6th grade who, in the classroom, studied the contents related to the democratic Revolution of April 25th, 1974 through a literary work - "História de uma Flor" ("History of a Flower"), written by Matilde Rosa Araújo. The collected data evinces the formative potentialities of the realized dynamic of curricular articulation, since the children were able to make an individual reading, with meaning, evidencing the understanding of the selected literary text and, through it, appropriating other historical knowledge besides dates and names. Keywords: History Education; literature; history; curriculum articulation; Portugal.